BH4-deficient hyperphenylalaninemia in Russia. - Polina Gundorova; Irina A Kuznetcova; Galina V Baydakova; Anna A Stepanova; Yulia S Itkis; Victoria S Kakaulina; Irina P Alferova; Lidya V Lyazina; Lilya P Andreeva; Ilya Kanivets; Ekaterina Y Zakharova; Sergey I Kutsev; et al. (PLoS ONE)
A timely detection of patients with tetrahydrobiopterin (BH4) -deficient types of hyperphenylalaninemia (HPABH4) is important for assignment of correct therapy, allowing to avoid complications. Often HPABH4 patients receive the same therapy as phenylalanine hydroxylase (PAH) -deficiency (phenylketonuria) patients-dietary treatment-and do not receive substitutive BH4 therapy until the diagnosis is confirmed by molecular genetic means. In this study, we present a cohort of 30 Russian patients with HPABH4 with detected variants in genes causing different types of HPA. Family diagnostics and biochemical urinary pterin spectrum analyses were carried out. HPABH4A is shown to be the prevalent type, 83.3% of all HPABH4 cases. The mutation spectrum for the PTS gene was defined, the most common variants in Russia were p.Thr106Met-32%, p.Asn72Lys-20%, p.Arg9His-8%, p.Ser32Gly-6%. We also detected 7 novel PTS variants and 3 novel QDPR variants. HPABH4 prevalence was estimated to be 0.5-0.9% of all HPA cases in Russia, which is significantly lower than in European countries on average, China, and Saudi Arabia. The results of this research show the necessity of introducing differential diagnostics for HPABH4 into neonatal screening practice.